Autologous Hematopoietic Stem Cell Transplantation for Patients with Lymphoma-Associated Hemophagocytic lymphohistiocytosis - Yue Song (SAGE Publishing, 2021)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a severe or even fatal inflammatory status. Lymphoma associated hemophagocytic lymphohistiocytosis (LAHS) is a kind of secondary HLH (sHLH). It suffers the worst outcome among sHLH. Allo-HSCT is often considered necessary. Autologous stem cell transplantation (auto-SCT) is widely used in the treatment of lymphoma, especially for high-risk NHL. There have been no clinical reports on the use of auto-SCT in LAHS in the past 20 years. Methods: We retrospectively evaluated 12 LAHS patients who received auto-SCT at our center from January 2013 to January 2020. Follow-up started at the date of LAHS diagnosis and ended at the date of death or last examination. Overall survival (OS) was calculated from the diagnosis of HLH to death of any cause. Results: The median period between diagnosis and auto-SCT is 6.7 months. All 12 patients achieved remission after transplantation. Follow-up to 1 January 2021, 8 patients remained disease-free, 4 patients relapsed and 2 of them died eventually. The median follow-up time is 20.9 months, and the median overall survival time has not been reached yet. The 3-year OS rates was 71%. Compared with LAHS patients who did not undergo transplantation during the same period (median OS time is 3.4 months), patients who underwent auto-SCT had a significantly better prognosis ( P =0.001). Even if the lymphoma reaches CR after treatment, auto-SCT still provides a better prognosis compared to CR patients without transplantation ( P =0.037). Compared with lymphoma patients without HLH who underwent auto-SCT during the same period, they had a similar prognosis ( P =0.350). Conclusion: LAHS, as a common type in secondary HLH, may have a better prognosis after removing the trigger of HLH. In this study, the autologous transplantation in LAHS can significantly improve the prognosis, and provide LAHS a similar prognosis as high-risk lymphoma without HLH.